Spelling councils and their role in spreading Arab and Islamic culture. (Damascus University Journal of arts and humanities sciences, 2022)
The study deals with a historical overview of the dictation councils and their role in spreading Arab culture, the most prominent aspects of the development of Arab-Islamic civilization and their intellectual contributions, the tools for spreading Arab and Islamic culture, the emergence of education, schools and libraries, and the bright aspects of our Arab civilization left by our ancestors.
Keywords: overview; the culture